QUANTITATIVE PHYTOCHEMICAL TEST OF METHANOL EXTRACT OF TABAT BARITO LEAVES (Ficus deltoidea Jack.) - I Wayan Arya Krishnawan Firdaus; Asphia Rahmah; Maharani Laillyza Apriasari; Yusrinie Wasiaturrahmah (Dentino : Jurnal Kedokteran Gigi, 2023)
ABSTRACTBackground: Tabat barito is a medicinal plant that has long been used by various ethnic groups in Indonesia, especially on the islands of Sumatra and Kalimantan. The people of Kalimantan use tabat barito as a traditional medicine for women who have just given birth, enhance blood circulation and get energy. Tabat barito leaves contain alkaloids, flavonoids, steroids, and phenolic compounds. Because of its use only based on the results of community trials and passed down orally, scientific research is needed for the chemical content or compounds contained therein. It aims to determine the bioactive profile of plants that play a role in therapy and their use can be accounted for. Purpose: To analyze the quantitative phytochemical test results of the methanol extract of tabat barito leaves (Ficus deltoidea Jack.) 100% concentration. Methods: Non-experimental research with quantitative laboratory examination to determine sample content. Results: The results showed that the total alkaloids content 154.31 mg/ml, flavonoids 62.917 mg/ml, steroids 49.036, and phenolic 99.689 mg/ml. Conclusion: The methanol extract of tabat barito leaves showed the content of alkaloid compounds at 154.31 mg/ml, flavonoids at 62.917 mg/ml, steroids at 49.036 mg/ml, and phenolics at 99.689 mg/ml. The compound with the highest total content was alkaloid at 154.31 mg/ml and the compound with the lowest total content was steroid at 49.036 mg/ml. Keywords: gravimetric, tabat barito leaves, uv-vis spectrophotometry, quantitative phytochemical test